APPROPRIASI TEORI KRITIS OLEH PARA PEMIKIR MUSLIM - Hendragunawan Sardjan Thayf; Muhammad Mukhtasar Syamsuddin; Supartiningsih Supartiningsih (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2020)
Critical Theory, especially of the Frankfurt School variant, is one of the theoretical and methodological lenses used quite often by contemporary Islamic thinkers. One thinker who is explicit in his adoption and adaptation of the thinking of the Frankfurt School is Fawzia Gilani-Williams who proposes an "Islamic Critical Theory". This article responds to her thought and at the same time departs from it to explore further the acceptance of this neo-Marxist thought in the discourse developed by Muslim intellectuals. At the same time, this article provides a response to the Islamization project of this idea, but also shows that at the most basic critical point, there is a parallelism between the Islamic ideals and the ideological ideals of the Frankfurt School Critical Theory.